Entrepreneurship Based Islamic Boarding School Education Management in Shaping Students’ Independence: A Study at Manbaul Chikmah Islamic Boarding School, Wonosobo - Alfan Kamandanu; Ngarifin Shidiq; Rifqi Muntaqo; Muhamad Yusuf Amin Nugroho; Putri Rofi'atus Sholikhah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
This article aims to analyze Islamic boarding school educational management in developing students’ entrepreneurial skills at Manbaul Chikmah Islamic Boarding School, Kauman Sapuran, Wonosobo. The study employs a qualitative approach with a case study design, using observation, in-depth interviews, and documentation techniques. Data were analyzed thematically through processes of reduction, presentation, and conclusion drawing, with data validity ensured through triangulation and auditability. The findings indicate that effective educational management through planning, organizing, implementation, and supervision significantly strengthens entrepreneurship-oriented curricula and learning. Students’ skill development is realized through the integration of life skills programs, extracurricular activities, entrepreneurship training, and direct practice in pesantren business units, such as cooperatives, bookshops, Hajj and Umrah service bureaus, and rental services. These findings affirm the strategic role of pesantren in fostering students’ economic independence based on religious education and entrepreneurship.